Problems of mathematics subject integration into module studies - Saldauskienė, Jovita (Lietuvos matematikos rinkinys, 2012)
This article deals with relevant problems of mathematics’ subject studies in College. There are presented the development and essential issues of mathematics‘ subject integration into economics module studies. The presented analysis reveals further directions of mathematics quality improvement search.
Keywords: business mathematics; economics; module; programs; students; studies